Pembentukan Persuasif Dalam Struktur Naratif Pada Iklan Gopay Indonesia Versi Bumbu Rahasia Dari Bu Sisca Yang Bikin #Lebihenak - Alfiani Kristiana Dewi; Handriyotopo Handriyotopo (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
The concept of an advertisement aimed at modern society can no longer rely solely on the description of a product. Because basically people can find their own info from a product using their smartphone. Therefore, an advertisement must be designed in such a way that it really attracts potential consumers. Persuasive messages need to be packaged well in order to achieve the target to influence consumers to use the company's products. The research "Pembentukan Persuasif Dalam Struktur Naratif Pada Iklan Gopay Indonesia Versi Bumbu Rahasia Dari Bu Sisca Yang Bikin #LebihEnak " aims to find a persuasive formation of a product advertisement used by modern society, namely Gopay Indonesia e-money through narrative analysis of one of the advertising versions, namely Bumbu Rahasia dari Bu Sisca yang Bikin #Lebihenak. The research method used is descriptive qualitative by collecting data through documentation, observation, and literature study. This research uses narrative theory from Bordwell-Thompson which sees the narrative elements consist of plot and story, space, time, characters, and narrative. The results showed that the formation of persuasion to grow awareness and product introduction was formed from each narrative element.